Comparative organic geochemistry of shale deposits of northern Appalachian Basin - Nandini Kar; Kathryn Tamulonis; Richard W. Smith; Stella C. Woodard; Mark R. Noll; Reilly M. Blocho; Andre Brunette; William A. Heins (Petroleum Research)
The organic-rich black shales in the Appalachian basin are a vital producer of natural gas. In this study, we present new multiproxy geochemical data from the Ordovician and Devonian black shales in New York (NY) and Pennsylvania (PA). The samples include outcrop samples collected in NY (Utica Group and Marcellus Formation) and core samples from PA (Marcellus Formation, Skaneateles Formation, and Genesee Group). We combined organic geochemical data (% total organic carbon or %TOC, δ13Corg, C/N ratio, and lipid n-alkane distribution) with trace element (TE) data to identify the organic matter (OM) sources and depositional conditions. The TE analysis data shows that water conditions were variable during the deposition of these black shales, fluctuating between oxic and dysoxic conditions with occasional anoxia. There was probably a change from an open water condition (Co∗Mn = 0.2) during the deposition of the Flat Creek Formation to a more restricted exchange later during the deposition of the Indian Castle Formation (Co∗Mn = 2.9) in the Ordovician. Basin circulation likely remained restricted during the deposition of the Devonian black shales (Co∗Mn ranges from 0.4 to 1.3). Based on δ13Corg values (−32.9‰ and −29.6‰) that are more depleted than marine OM δ13Corg, C/N ratios (11.2 and 9.2) higher than marine OM, and the presence of longer chain n-alkanes in the range of C25 to C33, we suggest that bryophytes were possibly a significant organic source to the Ordovician Utica Group in NY. The kerogen type in Utica Group samples is type III, mostly terrestrial OM. The Devonian NY and PA samples show mostly bimodal distributions. In some samples, a secondary, though sometimes dominant, shorter chain peak in the range of C14 to C20 is present, in addition to the long chain peak. We suggest the bimodal n-alkane distribution signifies a mixed OM source consisting of terrestrial and marine contributions with differing degrees of thermal maturation compared to the samples with a unimodal distribution. Our results suggest that samples from the NY Marcellus Group are composed of type III kerogen, while samples from the PA Marcellus Formation, Skaneateles Formation, and Genesee Group contain both type II and type III kerogens.